2021
DOI: 10.3390/polym13162702
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Critical Parameters for Carbodiimide Mediated Production of Highly Modified Chitosan

Abstract: An optimization of the 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and hydroxy benzotriazole mediated conjugation of the polysaccharide chitosan with functional carboxylic acids was shown. Optimal parameters that enable resource-efficient synthesis of highly functionalized chitosan were identified. In particular, use of only catalytic instead of stoichiometric amounts of hydroxy benzotriazole and tight control of pH in reaction mixture resulted in highly efficient incorporation of the desired moieties as si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…[ 36 ] Used parameters were optimized for high DS at maximal coupling efficacy (CE). [ 33 ] A brief description of the method can be found in Figure S5 of the Supporting Information for the exemplified case of CS‐Az‐16‐Bio‐16. The molecular structure of CS, CS‐Az, and CS‐Az‐Bio is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 36 ] Used parameters were optimized for high DS at maximal coupling efficacy (CE). [ 33 ] A brief description of the method can be found in Figure S5 of the Supporting Information for the exemplified case of CS‐Az‐16‐Bio‐16. The molecular structure of CS, CS‐Az, and CS‐Az‐Bio is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Modification of CS with substituents, containing carboxylic acid groups such as azide, biotin, or methyl red was accomplished using an amide coupling reaction facilitated by EDC and HOBt [33] based on the works of Matsumoto et al [36] Used parameters were optimized for high DS at maximal coupling efficacy (CE). [33] A brief description of the method can be found in Figure S5 of the Supporting Information for the exemplified case of CS-Az-16-Bio-16. The molecular structure of CS, CS-Az, and CS-Az-Bio is shown in Figure 1.…”
Section: Purification Modification and Characterization Of Highly Mod...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that these reactions are pH-sensitive. It has been suggested that the pKa values of amino groups can be used to optimize the amidation [ 117 ], but it has also been reported that the use of cosolvents, such as dimethyl sulfoxide (DMSO), can cause changes in the apparent pKa value of the reagents, changing their properties in the reaction [ 118 ]. Therefore, the starting pH value and nature and amount of cosolvents, along with other parameters such as temperature, the ratio of molar equivalents, MW and DD of CS, and reaction time, should be considered when planning EDC-based reaction conditions.…”
Section: Conjugation Of Chitosan and Hydroxycinnamic Acidsmentioning
confidence: 99%
“…The computer is connected to a touch display that can be utilized to operate the analytical software [ 13 , 14 ]. This system is applicable in, for instance, reaction optimization by in situ measurements of pH value and temperature [ 15 ], air-quality tests by measuring CO 2 concentration [ 16 ], hydrogen detection during photocatalytic water splitting [ 17 ], and general chemistry education [ 13 , 14 , 18 ], for which it was originally developed.…”
Section: Introductionmentioning
confidence: 99%